Transforming growth factor‐β signaling enhancement by long‐term exposure to hypoxia in a tumor microenvironment composed of Lewis lung carcinoma cells. Issue 11 (14th October 2015) - Furuta, Chiaki; Miyamoto, Tatsuki; Takagi, Takahiro; Noguchi, Yuri; Kaneko, Jyunya; Itoh, Susumu; Watanabe, Takuya; Itoh, Fumiko
Abstract : Transforming growth factor‐β (TGF‐β) is a potent growth inhibitor in normal epithelial cells. However, a number of malignant tumors produce excessive amounts of TGF‐β, which affects the tumor‐associated microenvironment by furthering the progression of tumorigenicity. Although it is known that the tumor‐associated microenvironment often becomes hypoxic, how hypoxia influences TGF‐β signaling in this microenvironment is unknown. We investigated whether TGF‐β signaling is influenced by long‐term exposure to hypoxia in Lewis lung carcinoma (LLC) cells. When the cells were exposed to hypoxia for more than 10 days, their morphology was remarkably changed to a spindle shape, and TGF‐β‐induced Smad2 phosphorylation was enhanced. Concomitantly, TGF‐β‐induced transcriptional activity was augmented under hypoxia, although TGF‐β did not influence the activity of a hypoxia‐responsive reporter. Consistently, hypoxia influenced the expression of several TGF‐β target genes. Interestingly, the expressions of TGF‐β type I receptor (TβRI), also termed activin receptor like kinase‐5 (ALK5), and TGF‐β1 were increased under the hypoxic condition. When we monitored the hypoxia‐inducible factor‐1 (HIF‐1) transcriptional activity by use of green fluorescent protein governed by the hypoxia‐responsive element in LLC cells transplanted into mice, TGF‐β‐induced Smad2 phosphorylation was upregulated in vivo . Our results demonstrate that long‐term exposure to hypoxia might alter responsiveness to TGF‐β signaling and affected the malignancy of LLC cells. Abstract : When we monitored the hypoxia‐inducible factor‐1 (HIF‐1) transcriptional activity by use of green fluorescent protein governed by the hypoxia‐responsive element in LLC cells transplanted into mice, TGF‐β‐induced Smad2 phosphorylation was upregulated. It indicated that hypoxia potentiates TGF‐β/Smad signaling in vivo .